PENGARUH PELATIHAN TERHADAP KINERJA PERAWAT DENGAN MOTIVASI SEBAGAI VARIABEL MODERASI (Studi pada RSUD Dr. Saiful Anwar Malang) - Siti Umi Ernawati (Universitas muhammadiyah malang, 2012)
Siti Umi ErnawatiRSUD Dr.Saiful Anwar MalangE-mail: erna.bachtiar@yahoo.co.idABSTRACTResearch with the title “The Effect of Training on Performance Motivation as a nurse with Variablemoderation. The purpose of this study was to determine the effect of training on the performance ofnurses in the RSSA, the influence of motivation on the performance of nurses in the RSSA, as well as todetermine the influence of motivation, influence the performance of nurse training in the RSSA Malang.Variables mentioned above were analyzed on several theories. Methods of research carried out bystatistical tests using SPSS to analyze the effect of training on performance, the influence of motivationon performance, as well as the role of motivation to the influence of training to performance. Theresults showed that training had a significant influence on the performance of nurses in the RSSA.While the motivation had no effect on performance and not be able to be moderating influence on theperformance of nurse training in the RSSA.Keywords: training, motivation, and nurses performance